The role of internal corporate social responsibility in promoting employees' commitment in Egypt - Abdel Wahab, Mahmoud (AUC Knowledge Fountain, 2016)
This thesis highlights the importance of internal corporate social responsibility that can promote employees’ commitment to their workplace in Egypt. This study hypothesized that organizations that have high turnover rates fail to provide sufficient care towards their employees. This lack of attention comes in the form of no trainings, attractive incentives, and unsatisfactory health care insurances. Moreover, in some cases employees are forced to submit resignations at the first day of work as a condition to work. Organizations that look after their employees in terms of good health care insurance, staff trainings, continuous coaching, and employee activities engagement- turn to have very low turnover rates. The significance of internal CSR comes in the form of preserving staff commitment through maximum engagement of employees, transparency, positive working environment, and work life balance. Interviews were conducted with 35 non-managerial employees in private organizations and five managerial level directors. The qualitative analyses of the findings reveal that most employees who left the company were looking after better packages and due to lack of organizational attention, whereas companies that heavily invest in its employees were able to retain and preserve them. The thesis concludes by providing some recommendations for companies to better retain its employees, such as having voice of the employees heard and reflected into the organization policies, provide transparency and access to information, foster positive working environment and finally to make work-life balance.